Clinical Use of Measuring Trough Levels and Antibodies against Infliximab in Patients with Pediatric Inflammatory Bowel Disease - So Yoon Choi; Ben Kang; Jee Hyun Lee; Yon Ho Choe (Gut and Liver, 2017)
Background/AimsThe clinical use of measuring infliximab (IFX) trough levels (TLs) and antibodies against IFX (ATIs) in patients with pediatric inflammatory bowel disease (IBD) remains unclear. We propose measuring these variables to create individual IFX treatment strategies for patients with pediatric IBD.Methods : This retrospective study was conducted in pediatric patients with IBD who received IFX from July 2009 to June 2014.Results : Samples were available from 39 patients with pediatric IBD. A significant difference was observed in IFX TLs in 16 patients who were in clinical remission (group A) after IFX therapy (median, 3.99 μg/mL; interquartile range [IQR], 0.30 to 21.96) compared to 23 patients who had a poor response to treatment (group B) (median, 0.88 μg/mL; IQR, 0.00 to 6.80, p=0.002). In group B, 21 patients underwent empiric intensification of IFX treatment. After dose intensification, 17 patients had an improved response to treatment. Four patients still had no response to dose intensification. Therefore, these patients were switched to other biologics.Conclusion : sPatients who had poor responses and subtherapeutic IFX TLs had an improved response to dose intensification. Patients who had ATIs were likely to continue to have no response after dose intensification. Therefore, tailoring individual IFX treatments based on IFX TLs, ATIs, and the clinical response should be considered.